Content of fatty acids in lipids of adipose derived mesenchymal stem cells - L. V. Kladnytska; V. S. Velychko; V. A. Tomchuk; V. Z. Salata; S. V. Velychko; N. V. Dyshlyuk; T. A. Mazurkevich; S. V. Midyk; R. R. Bokotko; T. L. Savchuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The content of fatty acids in the lipids of mesenchymal stem cells of dog adipose tissue culture was studied. Mesenchymal stem cells of dog adipose tissue culture were obtained by culturing the primary material in a CO2 incubator with a content of 5 % CO2, at a temperature of 37 °C in DMEM medium with the addition of 10–15 % fetal bovine serum and 1 % antibiotic-antimycotic. When the confluency of the monolayer reached 70–80 %, the cells were transferred to a suspension and subcultivated in order to reduce the heterogeneity of the culture and obtain a sufficient amount of biological material. The lipids of the obtained stem cells were analyzed for the content of fatty acids by the method of thin-layer gas-liquid chromatography. Determination of the content of lipids of fatty acids in FSK of a cat was carried out by the Folch method. A mixture of fatty acid methyl esters was analyzed on a Trace GC Ultra gas chromatograph with a flame ionization detector on a capillary column SPTM –2560, 100 m x 0.25 mm ID, 0.20 μm film (Supelco). Identification of fatty acids was carried out using a standard sample of Supelco 37 Сomponent FAME Mix. Quantitative assessment of the LC spectrum was carried out by the method of normalization of the peak planes of methylated LC derivatives and their content was determined as a percentage of the total content of all LC. The conducted study of the content of fatty acids in lipids made it possible to reveal certain features of the lipid metabolism of mesenchymal stem cells cultured in dog adipose tissue. A high content of oleic acid, characteristic of cells resistant to apoptosis and with high proliferative potential, was determined; a high ratio of unsaturated linoleic to saturated stearic acid (С18:1/С18.0), which reflects the high activity of the stearoyl-coenzyme-desaturase enzyme and, indirectly, the active state of the Wnt/β-catenin signaling pathway; inability to lengthen the chain of saturated fatty acids; lack or low activity of de novo synthesis of omega-6 polyunsaturated fatty acids. 18 fatty acids were found in the composition of lipids of fetal stem cells of a cat, of the saturated ones - the most palmitic acid (33.70 ± 0.02 %), of the monounsaturated ones – oleic acid (21.63 ± 0.03 %), of the polyunsaturated ones – linoleic acid (6.45 ± 0.07 %). The least amount of cis-,11,14-eicosadienoic acid (0.04 ± 0.01 %) was found in the composition of cell lipids. The total amount of saturated fatty acids in dog mesenchymal stem cell lipids was 65.65 ± 0.02 %), unsaturated fatty acids – 34.35 ± 0.02 %. Monoene fatty acids were determined in the amount of 24.46 ± 0.02 %, and polyene – 9.89 ± 0.02 %. The ratio index of polyunsaturated fatty acids ω 3 to ω 6 is 0.40. Lipids of mesenchymal stem cells of adipose tissue culture were characterized by a lower content of monoene unsaturated fatty acids 24.46 ± 0.02; (P < 0.05), with a higher content of ω3 fatty acids 3.04 ± 0.02 %; (P < 0.05), with a lower content of ω6 fatty acids 6.86 ± 0.02 %; (P < 0.05) in contrast to lipids of red bone marrow stem cells.